A Bus Schedule Application Using Fingerprint - Lakman, Siti Hanisah; Harun, Nur Ziadah (Applied Information Technology And Computer Science, 2024)
A bus schedule application mobile application with fingerprint verification is developed for UTHM students who use the shuttle bus service to make getting to class easier. Students previously encountered challenges such as missing the bus owing to a misunderstanding between the bus driver and the student. This proposed application acts as a communication medium between the bus driver and the student since it includes a location module that allows the bus driver to share the bus’s current location and the student to track it. The scheduling module where the bus timetable is provided, does help students arrive on time. Fingerprint characteristics are used to enhance the user experience by reducing login times and enhancing security. The methodology employed in this application is the prototyping model. Additionally, the user acceptance testing result are totally passed. Thus, the bus schedule applications simplify the process of arriving to class and make it more accessible